IMPROVING STUDENTS’ SPEAKING SKILL THROUGH DEBATE TECHNIQUE - Jonris Tampubolon (LPPM STKIP AL MAKSUM, 2020)
Speaking is considered as a necessary skill because of its essential role in facilitating students to master English. It enables students to express themselves creatively, imaginatively and to communicate with others effectively. To master speaking ability, students must be trained to use English in communication orally. One of the approriate and comprehensive strategies for teaching speaking is Debate Tehnique. The objective of this study is to find out whether the students’ speaking skill improves after being taught through Debate Technique or not. The strategy applied in this study was the aspect of speaking and debate technique. This study was conducted by using Quantitative Research. This study was done at SMA Dharma Pancasila Medan. There were 40 students taken as the sample in this study. The data were collected by giving speaking test to the students. The result of the test showed that the mean of score of the post-test was higher than the mean score of pre-test that was from 70 become 78.75. This means students’ speaking skill was improved after being thought by using Debate Technique.